Drug-induced veno-occlusive disease of the liver : unravelling the role of the inflammatory and coagulation pathways - Bruneau, Johanna C. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Haematology, 2008)
The thiopurines thioguanine (6TG) and mercaptopurine (6MP), along with Mylotarg (an antibody targeted agent), are used in the treatment of acute leukaemias. These drugs are more commonly associated with the development of Veno-Occlusive Disease (VOD) than any other therapeutic agent used in this patient group. Since VOD is known to be a pro¬coagulant and pro-inflammatory syndrome, we investigated the effect of these three drugs on the expression of Tissue Factor (TF), the initiator of blood coagulation, as well as the secretion of Tumour Necrosis Factor alpha (TNF-α) and Interleukin 8 (IL-8) in vitro. TF expression was determined by flow cytometry and cytokine secretion was quantified by sandwich ELISA. The cytotoxic effects of Mylotarg, 6TG and 6MP were investigated via the WST-1 assay. The apoptotic effects of 6TG and 6MP were measured by BrdU incorporation; the apoptotic effects of Mylotarg have been studied in detail previously, therefore were not repeated herein. The thiopurines were tested on three different leukaemic cell lines, representative of the different types of leukaemia that these agents would be used to treat: THPl (acute myeloid leukaemia), Jurkat E6.1 (T lymphoblastic leukaemia), and 697 (B cell precursor acute lymphoblastc leukaemia). HepG2, a hepatocyte cell line, was also used to determine the effect of these drugs on the liver. Mylotarg, a Cluster of Differentiation (CD) 33 specific antibody conjugated to the cytotoxic molecule calicheamicin, is used in the treatment of acute myelogenous and other CD33+ leukaemias. It was tested on the CD33+ THP1 cell line and the HepG2 cell line (CD33-).
Keywords: Haematology, Ph.D.; Ph.D. Trinity College Dublin